PkM (Pengabdian kepada Masyarakat): Pengembangan Paket Wisata di Desa Angsana, Setu, Jasinga, Bogor, Jawa Barat - Adelly Gabriella; Austin, Priscilla; Audrey Callista Candra; Nathanael, Marchellino; Setiawan, Budi (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
To enhance the local economy, tourism development through tourist villages requires the active participation of local residents. Angsana Tourist Village, located in Setu Village, Jasinga District, Bogor Regency, is one such village with great potential for further tourism development, thanks to its natural beauty and unique culture. However, the village still faces several challenges. The main challenges include inadequate promotion of previously designed tour packages and insufficient village funds to complete necessary infrastructure. To address these issues, a community service activity (PkM) was conducted by students from the Tourism study program, focusing on the renewal of existing tour packages and training in the use of social media platforms like Instagram and TikTok for promotional purposes. Through interviews and observations, the previous tour package was updated into the One Day Tour package in Angsana Tourist Village. Training on using TikTok and video editing with the CapCut app was also provided to improve the villagers' ability to promote the newly designed tour package. It is hoped that through these activities, Angsana Tourist Village will attract more tourists, thereby boosting the local economy.